25.1k views
24 votes
2x +4 (3 - 2x) = 3(2x + 2)/6 + 4
from my math book

User Meloun
by
6.1k points

2 Answers

4 votes

2x + 4(3-2x) = 3(2x+2)/6 +4

Break the brackets :

2x + 12 - 8x = (6x+6)/6 + 4

2x + 12 - 8x = x + 5

2x + 12 - 8x - (x+5) = 0
2x + 12 - 8x - x - 5 = 0
-7x + 7 = 0

-7x = -7
x = 1.

Hope it helps :)

User Reberhardt
by
5.9k points
2 votes

Answer:

x = 1

Explanation:

2x +4 (3 - 2x) = 3(2x + 2)/6 + 4

2x+12-8x = (6x+6)/6 +4

-6x + 12 = x+1+4

12-5 = 7x

7x = 7

x=1

Hope this helps!

User CMY
by
6.0k points